2013
DOI: 10.1002/jbmr.1863
|View full text |Cite
|
Sign up to set email alerts
|

Trends in hip fracture rates in Canada: An age-period-cohort analysis

Abstract: Age-standardized rates of hip fracture in Canada declined during the period 1985 to 2005. We investigated whether this incidence pattern is explained by period effects, cohort effects, or both. All hospitalizations during the study period with primary diagnosis of hip fracture were identified. Age-and sex-specific hip fracture rates were calculated for nineteen 5-year age groups and four 5-year calendar periods, resulting in 20 birth cohorts. The effect of age, calendar period, and birth cohort on hip fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 25 publications
0
35
1
Order By: Relevance
“…Nevertheless, New Zealand [7] and Sweden [8] have reported a continuous decrease in risk for younger cohorts but contrasting period effects with New Zealand showing a continuous increase versus a continuous decrease in Sweden. A recent study in Canada [10] also identified a decreased risk in younger cohorts and a non-linear effect of cohort in men. However, unlike our study, no fluctuations in risk were identified for birth cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, New Zealand [7] and Sweden [8] have reported a continuous decrease in risk for younger cohorts but contrasting period effects with New Zealand showing a continuous increase versus a continuous decrease in Sweden. A recent study in Canada [10] also identified a decreased risk in younger cohorts and a non-linear effect of cohort in men. However, unlike our study, no fluctuations in risk were identified for birth cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported the use of combined analysis to untangle the age-period-cohort (APC) effects [7][8][9][10]. The age effect in hip fracture incidence has been well described showing that the risk of fracture increases exponentially in the elderly [11].…”
Section: Introductionmentioning
confidence: 99%
“…Jean et al 13 analyzed whether the pattern observed by Leslie's group could be explained by a period effect, a birth cohort effect, or both. They appreciated significant period effects both in men and women.…”
Section: Usamentioning
confidence: 99%
“…Despite a declining trend in hip fractures in western countries (7)(8)(9)(10)(11), a worldwide increase is expected as a result of aging of populations by improving health care globally and increasing industrialization and urbanization (12). An increase in incidence of the first hip fracture implies that an increase in incidence of a subsequent hip fractures is to be expected as well.…”
Section: Introductionmentioning
confidence: 99%